2019
DOI: 10.1002/sctm.18-0216
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Lysate Improves Bone Forming Potential of Human Progenitor Cells Expanded in Microcarrier-Based Dynamic Culture

Abstract: Xenogeneic‐free media are required for translating advanced therapeutic medicinal products to the clinics. In addition, process efficiency is crucial for ensuring cost efficiency, especially when considering large‐scale production of mesenchymal stem cells (MSCs). Human platelet lysate (HPL) has been increasingly adopted as an alternative for fetal bovine serum (FBS) for MSCs. However, its therapeutic and regenerative potential in vivo is largely unexplored. Herein, we compare the effects of FBS and HPL supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 75 publications
(97 reference statements)
4
21
0
Order By: Relevance
“…Similar results were reported in different studies, and this is a turning point for the application of a scaffold with a peculiar chemical composition [46][47][48]. In fact, the structure and the materials must not interact with the vital function of the cells in order to be suitable for regenerative medicine application [49].…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported in different studies, and this is a turning point for the application of a scaffold with a peculiar chemical composition [46][47][48]. In fact, the structure and the materials must not interact with the vital function of the cells in order to be suitable for regenerative medicine application [49].…”
Section: Discussionsupporting
confidence: 83%
“…Several types of spinner flasks, including the Bellco spinner flask [ 18 , 24 , 25 , 30 , 31 , 33 ], Techne spinner flask [ 7 , 26 ], Corning spinner flask [ 29 ], and Cellspin spinning bottle [ 16 ] with capacity ranging from 100 ml to 125 ml, have been used for large-scale expansion of MSCs. Microcarriers were used to provide the growth surface for cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…All three studies reported that FBS was inferior compared to HPL and defined medium in promoting MSC proliferation. Instead of FBS, seven studies used 5%, 8%, or 10% (v/v) HPL [17,[19][20][21][22][23][24], one study used 5% (v/v) Ultragrow™ [25], and another one used 15% (v/v) AB human serum as supplement [26]. Defined culture mediums, i.e., MesenCult™-XF medium [27][28][29], StemPro® MSC SFM XenoFree medium [30][31][32][33], Corning® stemgro® hMSC medium [29], and PRIME-XV™ SFM medium [18], were used in seven studies ( Table 2).…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…Under xenogenic-free culture conditions, Gupta et al reported that HPL resulted in faster cell proliferation by 5.2 ± 0.61-fold in comparison to 2.7 ± 02.22-fold in FBS [60]. In addition, an automated serum-free, microcarrier culture system was established.…”
Section: Application Of Microcarriers In Msc Culture Msc Expansionmentioning
confidence: 99%